Effects of adriamycin and candesartan on the collagen and elastin of the aorta in rats - Uhm, Jae-Sun; Chung, Woo-Baek; Yoon, Jung-Sook; Oh, Yong-Seog; Youn, Ho-Joong (Clinical hypertension, 2014)
Introduction: It has been reported that the chemotherapeutic agent, adriamycin, not only has an effect on the myocardium but also on the arteries. The aim of this study is to elucidate effects of adriamycin and an angiotensin receptor blocker, candesartan, on collagen and elastin of the aorta in rats. Methods: Twenty four male 8-week-old Wistar-Kyoto rats were divided into four groups: control (C) group, adriamycin-treated (AD) group, candesartan-treated (CA) group, and adriamycin- and candesartan-treated (AD + CA) group. Adriamycin of 2.5 mg/kg/wk was administered intraperitoneally one time per week for 6 weeks, and candesartan of 10 mg/kg/day was administered orally everyday for 6 weeks. After 6 weeks, the rats were sacrificed and the aortas were harvested. Hematoxylin-eosin staining, Verhoff’s elastic, and Goldner’s trichrome staining were performed for histopathologic analyses. Tunica media thickness, collagen, and elastic area fractions were measured quantitatively with a computerized digital image analyzer. Results: Tunica media thickness in the CA and AD + CA groups was significantly lesser than that in the C and AD groups, respectively. The AD and AD + CA groups had a tendency of lower elastin area fraction than the C and CA groups, respectively. Collagen area fraction in the AD + CA group was significantly lower than that in the AD group. There were no significant differences of collagen/elastin ratio between groups. Conclusions: These findings suggest that adriamycin has a tendency of decreasing the quantity of elastin fibers and candesartan cannot mitigate the effects of adriamycin on elastin fibers. KCI Citation Count: 2